The Copernican question : prognostication, skepticism, and celestial order - Westman, Robert S. (Fletcher Jones Foundation humanities imprint., 2011)
In 1543, Copernicus defended his hypothesis that the Earth is a planet and the sun a body resting near the centre of a finite universe. This volume reframes this pivotal moment in the history of science, centring the story on a conflict over the credibility of astrology that erupted in Italy just as Copernicus arrived in 1496.